The essential Wooden : a lifetime of lessons on leaders and leadership - Wooden, John, 1910-2010 (McGraw-Hill, 2007)
"The Essential Wooden is the ultimate collection of Wooden's opinions and observations on achieving exceptional leadership in any organization, with 200 invaluable lessons for inspiring championship performance. From Wooden's earliest days as a leader through his legendary UCLA dynasty, The Essential Wooden distills a lifetime of learning into the leadership playbook for the twenty-first century."--Resource description page.